Propofol versus combined sedation in flexible bronchoscopy: a randomised non-inferiority trial - Daiana Stolz; Gabriel Kurer; Andrea H. Meyer; Prashant N. Chhajed; Eric Pflimlin; Werner Strobel; M. Tamm (2009)
Combined sedation with a benzodiazepine and an opiate has been proposed as standard sedation for bronchoscopy. Propofol is a sedative–hypnotic with a rapid onset of action and fast recovery time, but carries the potential risk of respiratory failure. Consecutive patients (n = 200) were randomly allocated to receive either the combination midazolam and hydrocodone or intravenous propofol. The primary end-points were the mean lowest arterial oxygen saturation during bronchoscopy and the readiness-for-discharge score 1 h after the procedure. The mean lowest arterial oxygen saturation during bronchoscopy did not differ across treatment groups (p = 0.422), and the number of patients recording an arterial oxygen saturation of ≤90% on at least one occasion was similar in both groups (p = 0.273). The median (interquartile range) readiness-for-discharge score 1 h after the procedure was significantly higher in the propofol group than in the combined sedation group (8 (6–9) versus 7 (5–9); p = 0.035). Patients assigned propofol exhibited less tachycardia during bronchoscopy and for ≥1 h after the examination. Minor procedural complications were noted in 71 (35.5%) patients and exhibited a similar incidence in both treatment arms (p = 0.460). Propofol is as effective and safe as combined sedation in patients undergoing flexible bronchoscopy, thus representing an appealing option if timely discharge is a priority.